Growth Response of Arctica Islandica to North Atlantic Oceanographic Conditions Since 1850 - Poitevin, Pierre; Thébault, Julien; Siebert, Valentin; Donnet, Sébastien; Archambault, Philippe; Doré, Justine; Chauvaud, Laurent; Lazure, Pascal (Frontiers in Marine Science, 2019)
The Northwest Atlantic is a key region with an essential role in global climate regulation, redistributing heat and influencing the carbon cycle. However, little is known about its evolution before 1950, mainly because of the lack of long-term instrumental measurements. The hard parts of long-lived marine biota hold the potential to extend instrumentally derived observation by several decades or centuries and enhance our understanding of global climate processes. Here, we investigate the effects of local, regional, and large-scale climate variability on the marine bivalve, Arctica islandica (Linnaeus, 1767) from Saint-Pierre and Miquelon (SPM). This archipelago lies at the boundary zone between the cold Labrador Current in the north and the warm Gulf Stream waters to the south, an excellent site to capture changes in North Atlantic climate and oceanography. This study presents the northernmost, statistically robust A. islandica growth chronology (1850–2015) from the Western North Atlantic and its potential as an environmental proxy record for past climatic and hydrographic variabilities at different time and geographical scales. In view of our results, it seems that A. islandica shell growth anomalies in SPM are mostly controlled by local primary production. Since long term instrumental records of this environmental variable are not available; we investigate the influence of global and regional environmental phenomena on A. islandica growth and indirectly on primary productivity of archipelago waters. The chronology correlates significantly and positively with the Atlantic Multidecadal Oscillation (AMO) and negatively with the North Atlantic Oscillation, two global climatic indices. The North Atlantic spatial pattern of correlation shows significant and positive correlations of 0–100 m temperatures from 1950 with A. islandica growth in SPM encompassing the subpolar gyre area. These global-scale relationships are refined and the mechanisms leading to them explained by comparing A. islandica growth chronology to regional environmental datasets. These relationships existing between the A. islandica shell growth record at SPM and environmental datasets covering different geographical scales could yield details about past North Atlantic basin and regional environmental conditions through their influence on SPM coastal environment.